La importancia del cuidado de enfermería para los pacientes de cáncer de pulmón - Hospital, Mª Luz (Psicooncología, 2006)
The aim of this paper is to acknowledge the relevance of nurse care and interventions regarding lung cancer patients. Systematic interventions designed from an integrative and holistic point of view, either as individuals or as a group, may improve quality of life of these patients by increasing satisfaction and wellbeing along the process.